Breeding Engineering, Producing And Marketing Laboratory Mice (Mus Musculus) As Animal Research - Oktavianie, Dyah Ayu (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Brawijaya, 2018)
The main problem is availability of animal research (stock) that at any time required by researchers or for practicum purposes. This problem actually can become a good breeding business opportunity for LBioS-UB that can cooperate with FKH-UB as one source of generating income and is very necessary to get independence of LBioS-FKH UB. LBioS has the modern facilities that very adequate to maintenance animal research, while FKH has experienced and competent human resources for breeding, production and provision of experimental animal stock. Based on the Brawijaya University policy, the long-term goals and targets of LBioS-UB should be self-supporting laboratories, especially in administration and finance. The University has provided sufficient facilities/equipment for research and production of biological materials, FKH UB is provide some experimental animals through breeding and producing in accordance with quality standards that have been identified and adjusted with the customer needs. The advantage of animal research produced by LBioS-PKH UB is the existing quality assurance and staff expertise. Promotion will be offered through networking that has been owned by several national/international institutions with website media: www.biosains.ub.ac.id and www.fkh.ub.ac.id